On Life Transitions, Loss, and Frailty: Aging according to Alessandra Macinghi negli Strozzi - Cayrol-Bernardo, Laura (Age, Culture, Humanities: An Interdisciplinary Journal, 2026)
Between 1447 and 1470, the Florentine patrician Alessandra Macinghi negli Strozzi (1408-1471) composed numerous letters to her sons, Filippo, Lorenzo, and Matteo, 73 of which have been preserved. Throughout her correspondence, she frequently referenced age and aging, expressing her own experiences of growing older, commenting on the ages of others, and framing people's appearances or behaviors in terms of age. This article explores how Alessandra perceived and articulated the experience of aging in her letters, shedding light on the subjective dimensions of later life. It examines intersecting discourses on aging, considering the various internalized meanings of age that emerge in different contexts. Additionally, it reflects on the impact of gender roles on life trajectories and the ways they shape personal and social expectations over time. The study further investigates generational dynamics within the Strozzi family, exploring how they evolved to accommodate the needs of an older family member.